Nutritional Quality of Eleven Leafy Vegetables Consumed in the Malagasy Highlands - Robijaona Rahelivololoniaina B (Britain International of Exact Sciences (BIoEx) Journal, 2023)
The Malagasy population generally consumes rice with "laoka" as a side dish. A diet that has become an atypical practice, a lifestyle well structured around the very common foods for typical Malagasy dishes. A nutritional analysis enabled us to determine their nutritional composition, and thus the energy intake that these foods can contribute to the proper functioning of the human metabolism for good health. A survey to assess the weekly consumption frequency of leafy vegetables by Tananarivians was carried out in 1,280 households. The constituent elements were then determined using TXRF for each elemental constituent of the solid samples. The macronutrient contents obtained from the analyses of these samples were used to determine overall energy values. Analysis of the extracts showed that most of them contained flavonoids and phenolic compounds respectively. Based on these results, Anatsinahy (Bidens pilosa) was found to be the most lipid-rich of the other brede species. Anamamy (Solanum nigrum) (38.88%) and Anandrano (Nasturtium officinale) (34.28%) are recommended for their high protein content. The carbohydrate content, ranging from 20.85% for Bidens pilosa to 52.69% for leaves of Ypomeas Batatas, could contribute to the nutrition, food security, and health of resource-poor people. The presence of these secondary metabolites in leafy vegetables may explain the particular pharmacological virtues of some of them, such as the alterative, antifungal, anti-inflammatory, antirheumatic, and styptic properties of Bidens pilosa, and the anesthetic, diuretic, digestive, sialagogue, antiasthmatic and antiscorbutic properties of Spilanthes acmella Murr. The presence of tannins, alkaloids, saponins, and flavonoids reported in this study may induce antidiarrheal activity.